Pyrolysis of cellulose mixed with ionic liquids 1-butyl-3-methylimidazolium bis(trifluoromethylsulfonyl)imide [bmim][TFSI], 1-butyl-3-methylimidazolium tetrafluoroborate [bmim][BF4], and 1-butyl-2, 3-dimethylimidazolium tetrafluoroborate [bmmim][BF4]. (March 2019) - Behrens, Michael; Cross, Jeffrey S.; Akasaka, Hiroki; Ohtake, Naoto
Abstract: In this research, cellulose was impregnated with ionic liquid as a pretreatment and then also used as a catalyst in the subsequent pyrolysis of the cellulose to produce a bio-oil. Impregnating cellulose with ionic liquid is expected to decrease the necessary pyrolysis temperature and improve the liquid bio-oil chemical composition. [bmim][TFSI], [bmim][BF4 ], and [bmmim][BF4 ] treated cellulose samples increased liquid yields at 225 °C to ∼15% compared to untreated cellulose with a liquid yield of 4% representing a ∼400% increase in liquid yield. However, as the pyrolysis temperature is increased, the advantage of using ionic liquid to increase liquid yield diminishes. FTIR analysis of the char shows that the pyranose ring structure breaks apart at a lower temperature for the ionic liquid pretreated cellulose. GC-MS analysis shows that the ionic liquids have different effects on the liquid composition and improve the composition of the bio-oil by decreasing acids and ketones. Based on these results, reaction pathways are discussed for the different ionic liquids. In this paper, a better understanding of how ionic liquid affects cellulose pyrolysis was achieved and explains how ionic liquids increased bio-oil yields at low temperatures. Highlights: Cellulose pretreated with ionic liquids were pyrolyzed at 225 °C, 250 °C, and 300 °C. The liquid products were analyzed with GC-MS and Karl Fischer Titrations while the char was analyzed with FTIR. The ionic liquids increase liquid yields at lower temperatures and improve the liquid quality. Mechanisms were proposed based off the FTIR and GC-MS results.